Bronchorrhoea--separation of mucus and serum components in sol and gel phases. - Lopez-Vidriero, M T (1979)
Bronchorrhoea sputum separates into two phases--sol and gel--at low speed centrifugation (5000 g), although higher speed (160 000 g) is required to obtain complete separation. Markers of mucus glycoprotein and serum transudate have been estimated in sputum, sol, and gel in five cases of bronchorrhoea associated with chronic bronchitis, asthma, or alveolar cell carcinoma. In all samples markers of both mucus glycoprotein and serum component were present in each phase. The concentration of serum markers was similar in both phases suggesting that it is to the serum that mucus glycoprotein is added. Since the volume of sol is greater, the total of serum components is higher in the sol than in the gel although, in total, a considerable amount was present in the gel. The fucose/sulphate ratio suggests that the glycoprotein in the sol is relatively more sulphated than is that of the gel, indicating that they may represent secretion from different cell types. The pattern of separation of two serum markers, IgA and transferrin, is different from that of albumin. Whether this is because they are locally produced or because they are selectively bound to mucus glycoprotein in the gel is not clear.